Determination of quantitative structure-property and structure-process relationships for graphene production in water - Nacken, Thomas; Damm, Cornelia; Xing, Haichen; Rüger, Andreas; Peukert, Wolfgang (Nano Research, 2015)
A scalable method for graphene and few-layer graphene (FLG) production by graphite delamination in aqueous solutions of the nonionic surfactant TWEEN®80 (TW80) using stirred-media mills is presented. Delaminated product analysis using statistical Raman spectroscopy yielded extensive processing-structure-property relationships that revealed how stress intensity and specific energy input, i.e., the process parameters, govern the yield of graphene production and defect formation. The dispersed carbon concentration increased but the content and the quality of the FLG product decreased sharply with higher specific energy input. The FLG content of the product was up to 90%, especially for low specific energy input. Moreover, Raman analyses revealed that stress intensities greater than about 1 nJ were related to significant defect formation in the product particles. Another key parameter for graphene production is solvent viscosity. The FLG concentration in the product increased by a factor of 10 when the solvent’s viscosity was increased from 1 to 6 mPa·s because shear- and friction-induced delamination was enhanced and in-plane fracture was reduced due to dampening of bead motion. Based on the processing-structure-property relationships found, we propose that the delamination process can be designed in such way that the product consists, almost totally, of FLG and that single-layer graphene is produced. The scalability of graphene production by stirred-media delamination was demonstrated when an increase in the batch size from 0.2 to 2 L had no significant effect on product quality. [Figure not available: see fulltext.]
Keywords: few-layer graphene; graphene; graphite delamination; process parameters; statistical Raman spectroscopy; stirred-media mill

Production of well dispersible single walled carbon nanotubes via a "floating catalyst"-method - Toni, Franziska; Xing, Haichen; Walter, Johannes; Strauß, Volker; Nacken, Thomas; Damm, Cornelia; Wirth, Karl-Ernst; Guldi, Dirk Michael; Peukert, Wolfgang (Chemical Engineering Science, 2015)
In this paper, we present a unique process chain for the production of single-walled carbon nanotubes (SWCNT) and document the relationship between the process parameters in gas phase production, the dispersibility of SWCNTs in aqueous solutions of sodium cholate and their properties. SWCNTs were prepared by a "floating catalyst" method using a solution of ferrocene in ethanol as precursor. Production rates in the range from 5 to 20. mg/h were achieved by using an optimized riser reactor design, which enables reduction of undesired wall-sticking of the catalyst particles and SWCNTs. Products featuring iron catalyst contents less than 30. wt% were obtained for low precursor concentrations in combination with short residence time in the reactor. Transmission electron microscopy (TEM) and statistical Raman analyses of the products reveal that the SWCNTs exhibit a diameter distribution ranging from 0.5 to 2.0. nm. Processing conditions, including precursor concentration, residence time, etc. were found to have only a slight impact on the mean geometric SWCNT diameter. Sonication based post-processing of the as-prepared SWCNTs in aqueous solutions of sodium cholate leads to an effective individualization of SWCNTs as proven by atomic force microscopy (AFM), 3D fluorescence spectroscopy, and by multi-wavelength analytical ultracentrifugation (AUC). Overall, the dispersibility of the non-purified SWCNTs in a 2. wt% aqueous solution of sodium cholate increases as the ferrocene partial pressure is decreased and, in turn, the catalyst concentration is reduced in the gas phase. Statistical Raman spectroscopy performed with the SWCNTs reveals that more than 75% of the produced carbon species are SWCNTs and that about 2/3 are semiconducting.
Keywords: Analytical ultracentrifugation and Raman spectroscopy; CNTs; Dispersion; Floating catalyst